Assessement of the Influence of Baking Fuel Types on the Residues of Some Heavy Metals in Selected Bread from Jalingo, Taraba State - Tutuwa, Jummai Adamu; David, Bando Christopher; Tadawus, Rejoice Habila; Ifraimu, Daniel; Aigbogun, Blessing Smart; Nuhu, Imbasire; Jesse, Polly Shingu; Agbu, Tsoken Danji (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
Method of food processing and handling plays pivoted role in its contamination. This research was geared towards assessing the level at which food handling and production processes influence metallic contamination. Samples of flour and baked bread (electric or coal oven) were sourced from market and bread bakeries within Jalingo metropolis. Heavy metals (Lead, Cadmium, Chromium, Nickel, Iron, and Zinc) analysis of the samples was done using Atomic Absorption Spectrophotometer (AAS). Bread baked using coal oven were observed to show elevated level of metallic contamination over those baked using electric oven with Iron (Fe) showing a statistical significant increase at p<0.05 while Cadmium (Cd) was not detected in bread baked using both fuel source. Both electric and coal baked bread were analyzed to have more metallic deposition when compared to the flour. Although, the heavy metals contamination were within the range of FAO/WHO permissible limit but long term consumption of such food products could lead to bioaccumulation in the biological system and becomes injurious to health.